(untitled) (Journal of Social Sciences Review, 2023)
The purpose of the quantitative correlational study was to investigate the association between students’ academic motivation and academic engagement. This study included 600 10th-grade students who were selected at random from 20 secondary schools in the district Lahore. The data from selected students were gathered using two research instruments. The independent sample t-test, Pearson r, and linear regression were used to analyze the data. As r =.781 (p > 0.01), the findings demonstrated a strong and significant correlation between academic motivation and students’ academic engagement. As a result, students’ academic engagement was positively impacted by academic motivation. Academic motivation and academic engagement of students differed significantly by gender. Policy makers, teachers, and scholars are advised to pay particular consideration to each learner’s level of academic engagement since it affects students’ engagement with schoolwork.